2015
DOI: 10.1037/pmu0000063
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the perception of bass in four concert halls.

Abstract: It is known that the perception of a warm and full sound in a concert hall requires a rich bass. However, earlier research offers an incomplete understanding on the perception of bass in concert halls, especially regarding how the excess attenuation of low frequencies due to seats affects the perception of musical instruments with low-frequency fundamentals. This article studies the level of perceived bass and its clarity in 4 concert halls via paired comparison listening tests. The results suggest that the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Bradley had estimated that the seat-dip effect can take away as much as 6 dB of the double bass sound at the 200 Hz octave band and he considers this detrimental to bass. To address this issue, in recent listening test the level and quality (in terms of articulation) of bass were assessed with some bass-register instruments with different seat-dip effect conditions 19 . In the first part of the test (N=9 subjects), short musical excerpts with double bass, cello, tuba, and trombone were used, and in the second part (N=13), the stimulus contained random individual notes from one of the instrument at a selected frequency range.…”
Section: Perception Of Bass-register Instruments In the Presence Of T...mentioning
confidence: 99%
“…Bradley had estimated that the seat-dip effect can take away as much as 6 dB of the double bass sound at the 200 Hz octave band and he considers this detrimental to bass. To address this issue, in recent listening test the level and quality (in terms of articulation) of bass were assessed with some bass-register instruments with different seat-dip effect conditions 19 . In the first part of the test (N=9 subjects), short musical excerpts with double bass, cello, tuba, and trombone were used, and in the second part (N=13), the stimulus contained random individual notes from one of the instrument at a selected frequency range.…”
Section: Perception Of Bass-register Instruments In the Presence Of T...mentioning
confidence: 99%
“…One such playing style is that low frequency instruments play slightly before other instruments * . Recently, we organized a brief listening test to find out whether the hall could emphasize such microtiming 16 . The results showed that subjects preferred the chords in which bass instruments were played 40 ms earlier than high violins and woodwinds.…”
Section: Proceedings Of the Institute Of Acousticsmentioning
confidence: 99%
“…A major driving force of research in auditorium acoustics from its earliest days to the present is the complex question of how sound is perceived by the listeners. The papers by Henna Tahvanainen et al (2015; “Studies on the Perception of Bass in Four Concert Halls”) and of Aki Haapaniemi and Tapio Lokki (2015; “The Preferred Level Balance Between Direct, Early, and Late Sound in Concert Halls”) pick up this question and focus on how spectral and temporal timbre is perceived in rooms. The stimuli used in both of these studies were derived from measurements that were collected in several renowned European concert halls using the authors’ so called “virtual orchestra.” The timbre of sounds in concert halls is strongly controlled by the properties of the room’s boundaries.…”
Section: Organization Of the Contributions: The Communication Chainmentioning
confidence: 99%